POTENSI PERLINDUNGAN HAK ATAS MEREK BAGI PELAKU USAHA SEKTOR KULINER DI WILAYAH KOTA BOGOR - Saepudin; Nurwati; J. Jopie Gilalo (Universitas Djuanda, 2024)
The research aims to find out and analyze the potential of legal protection for brands for business actors as well as the obstacles and efforts to overcome them according to Law Number 20 of 2016 concerning Trademarks and Geographical Indications, so as to find out legal protection efforts for brands for culinary sector business actors in Bogor City. The research method used in this study is empirical juridical which is analyzed qualitatively. From the research results it can be seen that the potential of legal protection for brands for business actors of the culinary sector consists of preventive legal protection and repressive legal protection. Barriers to culinary sector business actors in Bogor City in obtaining protection for their trademarks include the lack of understanding of culinary sector business actors regarding brands and their registration procedures, lack of counseling and outreach, expensive mark registration fees, and limited budget and experts in the field of IPR. Efforts to protect the law, namely through various policies, such as collaborating between the Director General of IP at the Ministry of Law and Human Rights and the Ministry of Cooperatives and SMEs in providing incentives for financing the registration of creative economy brand registration, as well as registration of collective marks for the creative economy industry